Nilai-Nilai Pendidikan Karakter dalam Cerpen Meraih Asa, Cita, dan Cinta Karya Nia Yurika Arisandi dan Kelayakannya Sebagai Bahan Ajar Teks Cerpen di SMP - Putri Dzakiyyatul Khotimah; Mukh Doyin (KOLONI, 2026)
Literary works are generally used as a medium to convey educational values and support the formation of student character. This study aims to describe the values of Education contained in the short story Meraih Asa, Cita, dan Cinta by Nia Yurika Arisandi and assess the feasibility of these values as learning materials for Junior High School students. This study uses qualitative descriptive method with reading, listening, and note-taking techniques. The results showed that the short story contains several educational values, namely the spirit of learning, hard work, learning achievement, responsibility, honesty, and motivation in achieving goals through education. In addition, these educational values are considered worthy of being used as teaching materials because they are delivered through simple language, contexts that are in accordance with the psychological development of students, and cultural backgrounds that are close to the lives of Junior High School students.